B-FRESH: DESIGN AND DEVELOP THE MARKETING PROCESS FRUIT COMMODITIES WITH HEDGING SYSTEMS TO PROTECT PRICES WHEN THE HARVEST - Anak Agung Gde Satia Utama; Elfrida Realisani (Journal of Management and Business, 2018)
Farmers always get a selling price that is much lower than the cost that they incur so they are forced to lose it. So far, farmers always believe in the prices offered by middlemen or collectors, even though the prices offered do not necessarily cover the expenses of farmers. To solve this problem, a B-fresh system was created that can protect farmers' hard work by hedging or hedging the harvest price. Commodities that are protected by price are fruit commodities because these commodities are still vulnerable to market price game. The development of this system requires cooperation with BUM Desa (Village-Owned Enterprises) as an operator so that this system can run well and properly. This system will process hedging automatically by determining the hedging price to be adjusted to the farmer's land area multiplied by the estimated fair value. BUM Desa (Village-Owned Enterprises also acts as an intermediary for third parties using an e-commerce system to market products and inform product details to consumers that are already present inside this B-fresh system.